Examining the Association Between Citizenship and Ethnicity on Identity Theft Risk: Findings from the National Crime Victimization Survey - Maher, Cooper A. (American journal of criminal justice, 2024)
Studies examining citizenship, ethnicity, and victimization risk have offered mixed findings. Despite this, works have largely focused upon direct-contact victimization, and do not offer insights into how this risk may vary across these dimensions for other crimes not characterized by direct contact, such as identity theft. This lack of understanding undermines abilities to tailor policies to effectively support vulnerable persons, and may potentially elevate risk of this costly crime among marginalized groups. Given this, the study aims to examine the associations between citizenship status, ethnicity and identity theft risk. Using a sample from the 2018 National Crime Victimization Survey’s Identity Theft Supplement (n = 71,984), logistic regression analyses examined the odds of identity theft. Lacking citizenship was associated with decreased odds of identity theft victimization, as was Hispanic ethnicity. However, Hispanic noncitizens faced higher relative risk than either noncitizens or Hispanic persons individually. Noncitizens’ decreased relative risk may stem from avoidance behaviors which reduce their suitability or exposure through a lifestyle-routine activities perspective. Hispanic noncitizens’ increased risk relative to others may stem from their doubly marginalized status. Future work is needed considering avoidance behaviors and citizenship status, to more clearly understand how these factors influence relative risk of victimization.